Eukaryote microbes potential for bioflocs in the swamp aquaculture - Marini Wijayanti; Tanbiyaskur; Dade Jubaedah; Ade Bayu Saputra; Karta Sari Genti; Agustina; Nabila Saraswati; Siti Yuliani; Hary Widjajanti (Jurnal Akuakultur Indonesia)
ABSTRACT